Preparation method of multi-cation co-doped O3-NaNi1 / 3Fe1 / 3Mn1 / 3O2 layered sodium ion battery positive electrode material
By using transition metal-position multiple cation co-doping and ball mill-assisted solid phase methods in O3-type layered sodium ion battery positive electrode materials, the material's shortcomings in energy density and diffusion kinetics are solved, and higher electrochemistry is achieved Performance and stability, suitable for industrial applications.
Patent Information
- Application Number
- CN202310768546.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-28
- Publication Date
- 2024-12-31
AI Technical Summary
The existing O3-type layered sodium ion battery positive electrode materials perform poorly in terms of energy density and diffusion kinetics, and have sodium residue and unstable electrode/electrolyte interface problems, which limits its application potential.
Using the method of co-doping of multiple cations at transition metal positions, NaMxNi(1/3-x)NyFe is prepared by replacing part of Ni ions by Cu ions and Al ions with Al ions. (1/3-y)Mn1/3O2 material improves the stability and electrochemical properties of the material.
The electrochemical performance of the material is significantly improved, including higher capacity, good rate performance and cycle stability, and the preparation method is simple and low-cost, with good industrial application prospects.
Smart Images

Figure HSA0000297112510000011 
Figure HSA0000297112510000021 
Figure HSA0000297112510000031
Abstract
Description
Technical Field
[0001] The invention belongs to the field of preparation of sodium ion battery electrode materials, and particularly relates to a transition metal site multiple cation co-doped modified O3 type layered sodium ion battery positive electrode material and a preparation method thereof. Background Art
[0002] Energy storage technology can power smart electronics, hybrid vehicles, grid applications, etc. It has changed our lifestyle in many ways and laid the foundation for the next era of the Internet of Things. Lithium-ion batteries are most widely used in our daily lives due to their high theoretical capacity and good cycle performance. However, the scarcity and uneven geographical distribution of lithium resources (20ppm) in the earth's crust currently lead to high prices for lithium, and the low abundance is not conducive to sustainable development. In addition to lithium-ion batteries, sodium-ion batteries also show relatively high capacity, and the sodium reserves are 2.09%, and sodium resources can be sustainably used, so the cost of sodium is lower than that of lithium. Similar to lithium-ion batteries, sodium-ion batteries (SIBs) are also composed of a cathode and an anode mounted on a current collector, and the electrochemical mechanism is also based on Na + shuttling between the cathode and the anode. In addition, aluminum can act as a + The anode current collector of the ion battery further reduces the cost of the energy storage device.
[0003] The cathode materials of sodium-ion batteries mainly include layered oxides, polyanionic compounds, Prussian blue analogs and metal organic materials. Among these cathode materials, layered oxides are widely studied due to their high theoretical capacity, easy synthesis and environmental harmlessness. Compared with lithium-ion batteries, sodium-ion batteries perform poorly in terms of energy density and diffusion kinetics because the weight of Na (Li: 6.9 g mol -1 , Na: 23 g mol -1 ), ionic radius (Li + : Na + : ) and standard electrochemical potential (Li: -3.04V, Na: -2.71V.vs. standard hydrogen electrode) are relatively higher than Li. These intrinsic factors limit the application of layered oxide cathode materials for sodium ion batteries. At the same time, how to overcome these problems is also extremely important. At present, the mainstream optimization methods include element doping, surface coating, and structural regulation with unique morphology and nanostructure, so as to improve air stability, reduce interface side reactions, inhibit phase change, improve structural reversibility, Na + kinetics and excellent overall electrochemical performance. The general formula of layered oxides is Na xTMO2 can be divided into two types according to its crystal structure: P2 type (0.3<x<0.7) and O3 type (0.7<x<1). + The coordination environment and oxygen layer stacking arrangement of the letter "P" and "O" represent Na + Accommodated in prism (P) and octahedron (O) positions; the numbers "2" and "3" represent the number of TM layers repeated in one unit cell. x TMO2 materials are generally synthesized by calcination at high temperatures. Since sodium evaporates at high temperatures, it is necessary to add additional sodium to compensate for the loss of sodium, but the additional sodium may cause a small amount of sodium residue in the target product, which is extremely detrimental to battery performance. In 2018, Zheng et al. studied NaNi 0.5 Mn 0.5 The effects of O2 storage in various atmospheres are investigated and ethanol / water washing is proposed to remove residual sodium compounds. These sodium residues will make the particle surface more susceptible to water absorption when exposed to air. 0.5 Mn 0.5 O2 will pass through Na + / H + The exchange process completely destroys its structure, while washing with ethanol does not cause any damage to its structure. Of course, H2O molecules in the crystal structure are not always detrimental to the electrochemical performance of sodium-ion batteries. For example, Choi et al. reported a Na 0.71 The crystalline water molecules in the cathode material of MnO2-0.25H2O not only serve as interlayer pillars to expand the interlayer distance of sodium ions, but also provide electrostatic charge shielding, improving its structural stability. In addition, the unstable electrode / electrolyte interface will also lead to a rapid decrease in capacity and voltage deterioration of sodium ion batteries. + The radius and mass are larger, in Na + The deintercalation process usually involves a slow Na + dynamics and large volume changes, so electrode materials with unique morphology and nanostructure are beneficial to expand the contact area of electrode / electrolyte and shorten the Na + The diffusion length of O3-Na[Li 0.05 Ni 0.3 Mn 0.5 Cu 0.1 Mg 0.05 ]O2 nanosheets, this method of combining chemical substitution with structural design can suppress the complex multiphase transformation under high voltage and lead to an increase in the ratio and thickness of the {010} plane. Sun et al. proposed a dry ball milling method to prepare O3-NaNi 0.6 Co 0.2 Mn0.2 O2 surface modified with nano-sized Al2O3 particle coating to prevent transition metal dissolution. Zhang et al. also successfully synthesized Cu by high temperature calcination. 2+ O3-doped dual-phase NaMn 0.48 Fe 0.32 Cu 0.2 O2 layered oxides, the optimized materials show high Na + diffusion coefficient and excellent sodium storage performance, and has good air stability. Summary of the invention
[0004] In view of the defects of the existing O3-type layered sodium ion battery positive electrode materials, the first object of the present invention is to provide an O3-type sodium ion battery layered positive electrode material NaM with excellent electrochemical performance and co-doped with multiple cations at the transition metal site. x Ni (1 / 3-x) N y Fe (1 / 3-y) Mn 1 / 3 O2 (M=Zn, Cu, Mg, etc.; N=Co, Ce, Ga, Al, Cr, etc.; where 0≤x≤0.33, 0≤y≤0.33) aims to improve the electrochemical properties of the material.
[0005] The second object of the present invention is to provide a method with good repeatability, simple operation and low cost for preparing the O3 type sodium ion battery layered positive electrode material co-doped with multiple cations in the transition metal position. The ball milling assisted solid phase method used in the present invention can be used as a simple manufacturing method to produce layered oxide positive electrode materials with good electrochemical properties.
[0006] The third object of the present invention is to adopt a method of co-doping multiple cations at the transition metal position, by replacing part of the Ni ions with Cu ions and part of the Fe ions with Al ions to improve the stability of the material. The doped cations stabilize the structure of the material and play a certain supporting role during the cycle, so that the material structure is further stabilized, thereby improving the electrochemical performance of the material.
[0007] The purpose of the present invention is achieved through the following technical solutions.
[0008] Doped O3-NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 layered sodium ion battery positive electrode material, characterized in that the material is modified and studied, and the chemical formula of the sodium ion battery positive electrode material is NaCu x Ni (1 / 3-x) Al y Fe (1 / 3-y) Mn 1 / 3O2, where 0.02≤x≤0.1, 0.02≤y≤0.03.
[0009] The above-mentioned method for preparing an O3 type sodium ion battery positive electrode material by co-doping multiple cations at the transition metal position comprises the following steps:
[0010] (1) According to the chemical formula NaM x Ni (1 / 3-x) N y Fe (1 / 3-y) Mn 1 / 3 The molar ratio of Ni, Fe, Mn, M and N elements in O2 is calculated by weighing the corresponding oxides and putting them into a ball mill for ball milling.
[0011] (2) Add 15 ml of ethanol to the ball mill and mix with the above oxides.
[0012] (3) During ball milling, rotate the ball in both forward and reverse directions alternately and mill overnight.
[0013] (4) The liquid obtained in step 3 is placed in an oven for drying, sieved, ground evenly, pressed into tablets, and then directly sintered in an air atmosphere and naturally cooled to room temperature to obtain the target product.
[0014] Furthermore, the oxides in step 1 are nickel oxide, ferric oxide, and manganese dioxide; and the oxides corresponding to M and N are copper oxide and aluminum oxide, respectively.
[0015] Furthermore, in step three, the rotation speed of the ball mill is 1200 r / min, and it is reversed after 20 minutes of forward rotation, and the ball milling beads and the material are mixed in a ratio of 1:1.5.
[0016] Furthermore, the tableting pressure in step 4 is 12 MPa.
[0017] Furthermore, in step 4, the sintering is carried out by heating the temperature to 900° C. at a heating rate of 5° C. / min and keeping the temperature for 12 hours.
[0018] Compared with the prior art, the present invention has the following advantages and technical effects:
[0019] 1. The present invention proposes a transition metal site multiple cation co-doped O3 type sodium ion battery positive electrode material NaM x Ni (1 / 3-x) N y Fe (1 / 3-y) Mn 1 / 3 O2, through the synergistic effect of M ions and N ions, replaces part of the nickel ions and iron ions of the material, inhibits multiphase transformation, stabilizes the crystal structure, and improves the electrochemical properties of the material.
[0020] 2. The method for preparing M and N ion co-doped O3 type sodium ion battery positive electrode material proposed in the present invention adopts ball milling assisted solid phase synthesis of precursors combined with high temperature calcination. It is simple, reliable and low-cost, and has good prospects for industrial application.
[0021] 3. The O3-type sodium ion battery positive electrode material NaM co-doped with multiple cations in transition metal positions proposed by the present invention x Ni (1 / 3-x) N y Fe (1 / 3-y) Mn 1 / 3 O2 is used in sodium ion batteries, with high specific capacity, good rate performance and cycle stability, and exhibits excellent electrochemical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 (a) and (b) are respectively the O3-type layered sodium ion battery positive electrode material NaNi prepared in Example 1 and Example 2 of the present invention. 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 and NaCu 0.04 Ni 0.29 Al 0.02 Fe 0.31 Mn 1 / 3 XRD pattern of O2.
[0023] Figure 2 (a) and (b) are respectively NaNi in Example 1 and Example 2 of the present invention. 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 and NaCu 0.04 Ni 0.29 Al 0.02 Fe 0.31 Mn 1 / 3 SEM image of O2.
[0024] Figure 3 (a) and (b) are respectively the O3-type layered sodium ion battery positive electrode material NaNi prepared in Example 1 and Example 2 of the present invention. 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 and NaCu 0.04 Ni 0.29 Al 0.02 Fe 0.31 Mn 1 / 3 The charge and discharge curves of O2 in the first two cycles at a voltage range of 2.0 to 4.0 V and 0.1 C.
[0025] Figure 4(a) and (b) are respectively the O3-type layered sodium ion battery positive electrode material NaNi prepared in Example 1 and Example 2 of the present invention. 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 and NaCu 0.04 Ni 0.29 Al 0.02 Fe 0.31 Mn 1 / 3 CV curve of O2.
[0026] Figure 5 (a) and (b) are respectively the O3-type layered sodium ion battery positive electrode material NaNi prepared in Example 1 and Example 2 of the present invention. 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 and NaCu 0.04 Ni 0.29 Al 0.02 Fe 0.31 Mn 1 / 3 Impedance diagram of O2. DETAILED DESCRIPTION
[0027] The above contents of the present invention are further described in detail below through examples, but this should not be understood as the scope of the above subject matter of the present invention being limited to the following examples, and all technologies implemented based on the above contents of the present invention belong to the scope of the present invention.
[0028] Example 1
[0039] (1) According to the synthesis of 1 mol of NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 The molar ratio of Na, Ni, Fe and Mn elements in O2 is as follows: Sodium carbonate (5% excess), nickel oxide, iron oxide and manganese dioxide are weighed, the weighed materials are placed in a ball mill, and ethanol solution is added dropwise to the ball mill to cover the materials, and the ball mill is carried out overnight.
[0030] (2) drying, grinding, and tableting the material obtained in step (1) at 80°C, heating the temperature to 900°C at a heating rate of 5°C / min in an air atmosphere, keeping the temperature for 12 hours, and then naturally cooling the temperature to 80°C before taking the material out of the muffle furnace. The obtained material is NaNi, an O3-type layered sodium ion battery positive electrode material. 1 / 3 Fe 1 / 3 Mn 1 / 3 O2.
[0031] Example 2
[0032] (1) According to the synthesis of 1 mol of NaCu 0.04 Ni 0.29 Al 0.02Fe 0.31 Mn 1 / 3 The molar ratio of Na, Ni, Fe, Mn, Cu and Al elements in O2 is as follows: Sodium carbonate (5% excess), nickel oxide, iron oxide, manganese dioxide, copper oxide and aluminum oxide are weighed, and the weighed materials are placed in a ball mill jar. Then, ethanol solution is added dropwise into the ball mill jar to cover the materials, and the ball mill is carried out overnight.
[0033] (2) The material obtained in step (1) is dried, ground, and pressed at 80°C, heated to 900°C at a heating rate of 5°C / min in an air atmosphere, kept warm for 12 hours, and then naturally cooled to 80°C before taking the material out of the muffle furnace. The obtained material is NaCu O3 type layered sodium ion battery positive electrode material 0.04 Ni 0.29 Al 0.02 Fe 0.31 Mn 1 / 3 O2.
[0034] Example 3
[0035] (1) According to the synthesis of 1 mol of NaZn 0.05 Ni 0.28 Ga 0.01 Fe 0.32 Mn 1 / 3 The molar ratio of Na, Ni, Fe, Mn, Zn and Ga elements in O2 is as follows: Sodium carbonate (5% excess), nickel oxide, iron oxide, manganese dioxide, zinc oxide and gallium oxide are weighed, and the weighed materials are placed in a ball mill, and then ethanol solution is added dropwise to the ball mill to cover the materials, and the ball mill is carried out overnight.
[0036] (2) The material obtained in step (1) is dried, ground, and pressed at 80°C, heated to 900°C at a heating rate of 5°C / min in an air atmosphere, kept warm for 12 hours, and then naturally cooled to 80°C before taking the material out of the muffle furnace. The obtained material is NaZn, an O3-type layered sodium ion battery positive electrode material. 0.05 Ni 0.28 Ga 0.01 Fe 0.32 Mn 1 / 3 O2.
[0037] Example 4
[0038] (1) According to the synthesis of 1 mol of NaNi 0.28 Ti 0.05 Fe 1 / 3 Mn 1 / 3 The molar ratio of Na, Ni, Fe, Mn and Ti elements in O2 is as follows: Sodium carbonate (5% excess), nickel oxide, iron oxide, manganese dioxide and titanium monoxide are weighed, and the weighed materials are placed in a ball mill. Then, ethanol solution is added dropwise to the ball mill to cover the materials, and the ball mill is carried out overnight.
[0039] (2) drying, grinding, and tableting the material obtained in step (1) at 80°C, heating the temperature to 900°C at a heating rate of 5°C / min in an air atmosphere, keeping the temperature for 12 hours, and then naturally cooling the temperature to 80°C before taking the material out of the muffle furnace. The obtained material is NaNi, an O3-type layered sodium ion battery positive electrode material. 0.28 Ti 0.05 Fe 1 / 3 Mn 1 / 3 O2.
[0040] Example 5
[0041] (1) According to the synthesis of 1 mol of NaSn 0.1 Ni 0.23 Fe 1 / 3 Mg 0.05 Mn 0.28 The molar ratio of Na, Ni, Fe, Mn, Sn and Mg elements in O2 is as follows: Sodium carbonate (5% excess), nickel oxide, iron oxide, manganese dioxide, tin oxide and magnesium oxide are weighed, the weighed materials are placed in a ball mill, and ethanol solution is added dropwise into the ball mill to cover the materials, and the ball mill is carried out overnight.
[0042] (2) The material obtained in step (1) is dried, ground, and pressed at 80°C, heated to 900°C at a heating rate of 5°C / min in an air atmosphere, kept warm for 12 hours, and then naturally cooled to 80°C before taking the material out of the muffle furnace. The obtained material is NaSn, an O3-type layered sodium ion battery positive electrode material. 0.1 Ni 0.23 Fe 1 / 3 Mg 0.05 Mn 0.28 O2.
[0043] Example 6
[0044] (1) According to the synthesis of 1 mol of NaMg 0.05 Ni 0.28 Al 0.02 Fe 0.31 Mn 1 / 3 The molar ratio of Na, Ni, Fe, Mg and Al elements in O2 is as follows: Sodium carbonate (5% excess), nickel oxide, iron oxide, manganese dioxide, magnesium oxide and aluminum oxide are weighed, and the weighed materials are placed in a ball mill. Then, ethanol solution is added dropwise to the ball mill to cover the materials, and the ball mill is carried out overnight.
[0045] (2) drying, grinding and tableting the material obtained in step (1) at 80°C, heating the material to 900°C at a heating rate of 5°C / min in an air atmosphere, keeping the temperature for 12 hours, and then naturally cooling the material to 80°C before taking it out of the muffle furnace. The obtained material is NaMgO3 type layered sodium ion battery positive electrode material.0.05 Ni 0.28 Al 0.02 Fe 0.31 Mn 1 / 3 O2.
[0046] Example 7
[0047] (1) According to the synthesis of 1 mol of NaZn 0.05 Ni 0.28 Ce 0.03 Fe 0.3 Mn 1 / 3 The molar ratio of Na, Ni, Fe, Zn and Ce elements in O2 is as follows: Sodium carbonate (5% excess), nickel oxide, iron oxide, manganese dioxide, zinc oxide and cerium oxide are weighed, and the weighed materials are placed in a ball mill, and then ethanol solution is added dropwise to the ball mill to cover the materials, and the ball mill is carried out overnight.
[0048] (2) The material obtained in step (1) is dried, ground, and pressed at 80°C, heated to 900°C at a heating rate of 5°C / min in an air atmosphere, kept warm for 12 hours, and then naturally cooled to 80°C before taking the material out of the muffle furnace. The obtained material is NaZn, an O3-type layered sodium ion battery positive electrode material. 0.05 Ni 0.28 Ce 0.03 Fe 0.3 Mn 1 / 3 O2.
[0049] Example 8
[0050] (1) According to the synthesis of 1 mol of NaSn 0.02 Ni 0.28 Co 0.1 Fe 0.23 Mn 1 / 3 The molar ratio of Na, Ni, Fe, Sn and Co elements in O2 is as follows: Sodium carbonate (5% excess), nickel oxide, iron oxide, manganese dioxide, tin oxide and cobalt oxide are weighed, and the weighed materials are placed in a ball mill. Then, ethanol solution is added dropwise to the ball mill to cover the materials, and the ball mill is carried out overnight.
[0051] (2) The material obtained in step (1) is dried, ground, and pressed at 80°C, heated to 900°C at a heating rate of 5°C / min in an air atmosphere, kept warm for 12 hours, and then naturally cooled to 80°C before taking the material out of the muffle furnace. The obtained material is NaSn, an O3-type layered sodium ion battery positive electrode material. 0.02 Ni 0.28 Co 0.1 Fe 0.23 Mn 1 / 3 O2.
[0052] Application Examples
[0053] The ion co-doped O3-type layered sodium ion positive electrode materials obtained in each embodiment were ground evenly with the conductive agent SuperP and the binder PVDF in a mass ratio of 8:1:1, and then an appropriate amount of NMP was added to make a slurry, and evenly coated on the pretreated aluminum foil, dried at 80°C in a blast drying oven for 1h, and then dried at 120°C in a vacuum drying oven for 12h; then cut into 12mm round positive electrode sheets with a cutting machine. A sodium metal sheet with a diameter of 12mm and a thickness of 0.2mm was used as the negative electrode, a 0.1mol / L sodium perchlorate / ethylene carbonate / dimethyl carbonate / fluoroethylene carbonate solution was used as the electrolyte, and a polypropylene film with a diameter of 12mm was used as the diaphragm. The CR2016 button battery was assembled in a glove box filled with high-purity argon. The electrochemical properties of the material were tested in the voltage range of 2.0 to 4.0V.
[0054] Figure 1 The XRD patterns shown in the figure show that they all have a layered structure, with sharp diffraction peaks and no other obvious impurity peaks. As can be seen from Figure (b), the peak shape of the XRD pattern of the positive electrode material co-doped with copper and aluminum is consistent with that in Figure (a), except that the position of the diffraction peak is slightly offset, indicating that copper ions and aluminum ions have been doped into the material.
[0055] Figure 2 The SEM images shown show that the primary particles of both materials have a flaky structure with a dense structure.
[0056] Figure 3 The voltage range shown in (a) is 2.0-4.0 V, and the current density is 120 mA / g when NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 The charge and discharge curves of O2 in the first two cycles. Figure 3 (b) is the charge-discharge curve of the first two cycles of the material doped with Cu and Al under the same conditions. It can be seen from the figure that the sodium ion battery prepared by the O3-type layered metal oxide positive electrode material modified by co-doping with Cu and Al ions has a higher degree of overlap and better stability.
[0057] Figure 4 (a) shows O3-NaNi at a voltage range of 2.0 to 4.0 V 1 / 3 Fe 1 / 3 Mn 1 / 3 CV curves of O2 layered metal oxide cathode materials. Figure 4 (a) It can be seen that O3-NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 layered metal oxide cathode materials have a pair of strong redox peaks and a pair of unclear redox peaks, indicating that the reversibility is not high. Figure 4(b) shows the NaCu in the voltage range of 2.0 to 4.0 V. 0.04 Ni 0.29 Al 0.02 Fe 0.31 Mn 1 / 3 The redox peaks of the three cycles of the O2 layered metal oxide positive electrode material are significantly sharper, and the cyclic voltammetry curves have a better overlap and higher reversibility, which also shows that copper and aluminum co-doping has good cycle stability.
[0058] Figure 5 O3-NaNi shown 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 and NaCu 0.04 Ni 0.29 Al 0.02 Fe 0.31 Mn 1 / 3 The impedance diagram of O2 layered metal oxide positive electrode material shows that the impedance is significantly reduced after copper and aluminum co-doping, indicating that copper and aluminum co-doping can improve the high-voltage O3-NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 The electrochemical reaction kinetics of O2 can be improved and good rate performance can be achieved.
[0059] The above embodiments describe the basic principles, main features and advantages of the present invention. The present invention is not limited by the above embodiments. The above embodiments and descriptions are only for illustrating the principles of the present invention. Without departing from the scope of the principles of the present invention, the present invention may have various changes and improvements, and these changes and improvements should also be regarded as the protection scope of the present invention.
Claims
1. Co-doping of transition metal sites with multiple cations to modify the positive electrode material of O3-type layered sodium ion battery, characterized in that The chemical formula of the positive electrode material of sodium ion battery is NaM x Ni (1 / 3-x) N y Fe (1 / 3-y) Mn 1 / 3 O2, (wherein, M=Zn, Cu, Mg, etc.: N=Co, Ce, Ga, Al, Cr, etc.; 0≤x≤0.33, 0≤y≤0.33).
2. A method for preparing a modified O3-type layered sodium ion battery positive electrode material by co-doping a plurality of cations on transition metals as claimed in claim 1, characterized in that The specific steps are: Step 1: According to the chemical formula NaM x Ni (1 / 3-x) N y Fe (1 / 3-y) Mn 1 / 3 O2, where (M = Zn, Cu, Mg, etc.; N = Co, Ce, Ga, Al, Cr, etc.; 0≤x≤0.33, 0≤y≤0.33) the molar ratio of Ni, Fe, Mn, M and N elements is weighed and the corresponding oxides are placed in a ball mill for ball milling; Step 2: Add 15 ml of ethanol to the ball mill and mix with the above oxides; Step 3: During ball milling, rotate forward and reverse alternately, and mill overnight; Step 4: Place the liquid obtained in step 3 in an oven for drying, sieve, grind evenly, press into tablets, and then directly sinter in an air atmosphere and cool naturally to room temperature to obtain the target product.
3. The method for preparing a modified O3-type layered sodium ion battery positive electrode material by co-doping a plurality of cations with transition metals according to claim 2, characterized in that: The oxide particle size in step 1 is small, and the ratio of ball milling beads to material is 1:1.
5.
4. The method for preparing a modified O3-type layered sodium ion battery positive electrode material by co-doping a plurality of cations with transition metals according to claim 2, characterized in that: In step 3, the rotation speed of the ball mill is 1200 r / min, and it rotates forward for 20 minutes and then reverses, alternating cycles.
5. The method for preparing a modified O3-type layered sodium ion battery positive electrode material by co-doping a plurality of cations with transition metals according to claim 2, characterized in that: In step 4, the sintering is carried out by heating the temperature to 900°C at a heating rate of 5°C / min, keeping the temperature for 12 hours, and naturally cooling to 80°C to obtain the O3 type layered sodium ion positive electrode material M, N doped O3 type layered sodium ion positive electrode material.
Citation Information
Cited By
P2 / O3 double-phase composite material, preparation method and application thereof, and sodium ion battery
CN119764431A
Modified zinc-iron-manganese-based layered oxides, their preparation and use in sodium-ion batteries
CN122930850A
